Evaluation of growth parameters and forage yield of Sugar Graze and Jumbo Plus sorghum hybrids under three different spacings during the maha season in the dry zone of Sri Lanka - Gnanagobal, H.; Sinniah, J. (Research gate, 2018)
A field experiment to evaluate the growth parameters and fodder yields of Sugar Graze and Jumbo Plus under occasional irrigation was conducted at 3 different plant spacings (30 × 15, 30 × 45 and 30 × 60 cm) on a red-yellow latosol in the dry zone of Sri Lanka from August 2015 to January 2016. The design was a randomized block with 3 replications. Initial harvesting of fodder was done 60 days after planting and 2 ratoon yields were assessed at successive 60-day intervals. Plant spacing was inversely related (P<0.05) to dry matter (DM) yield with the narrowest spacing (30 × 15 cm) producing yields of 14.1 t DM/ha for Sugar Graze and 12.6 t DM/ha for Jumbo Plus at the initial harvest. Plant spacing also influenced leaf area, stem girth, root length and plant height in the initial harvest. Sugar Graze produced higher yields than Jumbo Plus at the initial and second ratoon harvests. Yields from ratoon crops were about 30% of those for the initial harvest. Further studies are needed to determine how these findings apply under the low-rainfall conditions of the yala season, and chemical analyses and animal feeding studies would provide valuable information on the nutritional value of the different forages.
Keywords: Dry matter yield; Forage sorghum; Ratoon crop; Red yellow latosol; Row width